Wavelet analysis : basic concepts and applications - Arfaoui, Sabrine; Ben Mabrouk, Anouar; Cattani, Carlo, 1954- (Boca Raton : Chapman & Hall/CRC Press, 2021)
"Wavelet Analysis: Basic Concepts and Applications provides a basic and self-contained introduction to the ideas underpinning wavelet theory and its diverse applications. This book is suitable for master's or PhD students, senior researchers, or scientists working in industrial settings, where wavelets are used to model real world phenomena and data needs (such as finance, medicine, engineering, transport, images, signals etc.) Features Offers a self-contained discussion of wavelet theory Suitable for a wide audience of post-graduate students, researchers, practitioners, and theorists Provides researchers with detailed proofs Provide guides for readers to help them understand and practice wavelet analysis in different areas"--
OCLC-licensed vendor bibliographic record.
Keywords: Wavelets (Mathematics); MATHEMATICS / Functional Analysis; MATHEMATICS / Mathematical Analysis; MATHEMATICS / Applied